Development of photoactive biomaterial using modified fullerene nanoparticles - Saulėnienė, Gabrielė; Kirsnyte-Snioke, Monika; Stirkė, Arūnas; Jasulaitiene, Vitalija; Straksys, Antanas; Dobilaitis, Samuelis; Melo, Wanessa C. M. A. (Frontiers in Chemistry, 2024)
Medical device-associated biofilm infections continue to pose a significant challenge for public health. These infections arise from biofilm accumulation on the device, hampering the antimicrobial treatment. In response, significant efforts have been made to design functional polymeric devices that possess antimicrobial properties, limiting or preventing biofilm formation. However, until now none of the strategies showed a promissory effect. Thus, antimicrobial photodynamic therapy (aPDT) has been shown as a promising candidate to overcome this problem. Photosensitizers (PS) are the main key component for aPDT and fullerenes have been chosen as PS due to their good quantum yields and lifetimes spans. In this study, polylactic acid (PLA) surface was modified with fullerene (C60) and reaction was proven by XPS analysis. The biopolymer surface was characterized by AFM, SEM, and water contact angle measurements. The obtained results imply that the highest fullerene precipitation was attained when PLA was modified with ethylenediamine (EDA) before the reaction with C60, as the highest carbon increase was identified using XPS following reaction with C60. While samples' hydrophobicity decreased after PLA modification with EDA, it increased after fullerene precipitation. Which implies that bacteria have a lower propensity to attach. Although the surface of the samples became smoother following PLA modification with EDA and reaction with 0,1% C60 precipitation, with 1% C60 precipitation the surface roughness was comparable to unmodified PLA, according to AFM and SEM analyses. Fullerene-based biopolymers could potentially be used in aPDT to make antimicrobial surfaces or medical devices.